2013
DOI: 10.1128/mcb.00887-13
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A) Tail-Mediated Gene Regulation by Opposing Roles of Nab2 and Pab2 Nuclear Poly(A)-Binding Proteins in Pre-mRNA Decay

Abstract: The 3= end of most eukaryotic transcripts is decorated by poly(A)-binding proteins (PABPs), which influence the fate of mRNAs throughout gene expression. However, despite the fact that multiple PABPs coexist in the nuclei of most eukaryotes, how functional interplay between these nuclear PABPs controls gene expression remains unclear. By characterizing the ortholog of the Nab2/ZC3H14 zinc finger PABP in Schizosaccharomyces pombe, we show here that the two major fission yeast nuclear PABPs, Pab2 and Nab2, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…The results from the fractionation studies not only demonstrate that ZC3H14 binds to the ATP5G1 transcript in the nucleus but also provide evidence for a role in ensuring proper pre-mRNA processing of target transcripts prior to exiting the nucleus. These findings are consistent with a recent study in Schizosaccharomyces pombe that demonstrates a role for the fission yeast ortholog of ZC3H14, Nab2, in acting at the level of the unspliced pre-mRNA and preventing degradation by the nuclear exosome to ensure proper maturation of target transcripts (79). We hypothesize that the inability to ensure the proper nuclear processing of the ATP5G1 pre-mRNA results in a significant decrease in the levels of mature ATP5G1 mRNA in the cytoplasm due to rapid degradation of improperly processed ATP5G1 mRNA via NMD.…”
Section: Discussionsupporting
confidence: 93%
“…The results from the fractionation studies not only demonstrate that ZC3H14 binds to the ATP5G1 transcript in the nucleus but also provide evidence for a role in ensuring proper pre-mRNA processing of target transcripts prior to exiting the nucleus. These findings are consistent with a recent study in Schizosaccharomyces pombe that demonstrates a role for the fission yeast ortholog of ZC3H14, Nab2, in acting at the level of the unspliced pre-mRNA and preventing degradation by the nuclear exosome to ensure proper maturation of target transcripts (79). We hypothesize that the inability to ensure the proper nuclear processing of the ATP5G1 pre-mRNA results in a significant decrease in the levels of mature ATP5G1 mRNA in the cytoplasm due to rapid degradation of improperly processed ATP5G1 mRNA via NMD.…”
Section: Discussionsupporting
confidence: 93%
“…In the first case, the exosome promotes the trimming of the 3 ′ end to generate a mature snoRNA, while in the second, the premRNA is degraded (Lemay et al 2010;Lemieux et al 2011;Lee et al 2013). Our purification of Mtl1 also recovered the Nab2 poly(A)-binding protein (Supplemental Table S1), and a recent purification of Nab2 identified several NURS subunits (Grenier St-Sauveur et al 2013). Nab2 appears to antagonize the action of Pab2, Rrp6, Red1, and Mtl1 in rpl30-2 pre-mRNA degradation by competing with Pab2 for binding to the poly(A) tail (Grenier St-Sauveur et al 2013;Lee et al 2013).…”
Section: Nurs As An Integrator Of Rna Processing Signalsmentioning
confidence: 85%
“…Our purification of Mtl1 also recovered the Nab2 poly(A)-binding protein (Supplemental Table S1), and a recent purification of Nab2 identified several NURS subunits (Grenier St-Sauveur et al 2013). Nab2 appears to antagonize the action of Pab2, Rrp6, Red1, and Mtl1 in rpl30-2 pre-mRNA degradation by competing with Pab2 for binding to the poly(A) tail (Grenier St-Sauveur et al 2013;Lee et al 2013). Additionally, the gene encoding another NURS subunit, rmn1 + , exhibits a negative genetic interaction with nab2 + (Cho et al 2012).…”
Section: Nurs As An Integrator Of Rna Processing Signalsmentioning
confidence: 99%
“…Given the interdependent nature of transcription, RNA processing, export, and translation, dNab2/ZC3H14 could play direct roles in functions other than control of poly(A) tail length. Indeed, recent work has defined roles for the S. pombe Nab2 protein in regulated RNA turnover (Grenier St-Sauveur et al 2013) and other studies identified the corresponding C. elegans protein, termed Sut-2, as a suppressor of a Tau toxicity model (Guthrie et al 2009). Understanding the precise molecular functions of RNA-binding proteins, as well as defining their target RNAs, is a significant challenge and a major focus of our ongoing studies of dNab2/ZC3H14.…”
Section: Discussionmentioning
confidence: 99%